Aktivitas Anti Jamur 2,3-dihidroksipentadekanoat dari Kayu Mahalilis (Palaquium sp.) - Renhart Jemi; Wasrin Syafi; Fauzi Ferbianto'; Muhammad Hanafi (Jurnal Kimia Terapan Indonesia, 2012)
The objectives of this research were to evaluate the extractive content of hartdwood of mahalilis wood (palaquium sp.) and identification of bio-acttve compounds wood decay fungi. Mahalilis wood was macerated with MeOH and then partitioned in stages wiht the n-hexane, CHCI31 EtOAc and n-BuOH, respectively. The result of antifungal test, show the most active 14 fraction CHCl3 comparedfraction and negative controls (CCB and itraconazole). Purification of CHCl3 fraction was column chromatographedproduced five fraction (M-I-M-5). TheM2 active fraction shown inhibited the growth to Schizophyllum communeFries withIC(so) is 56ppm and Pleurotus ostreatus with IC(so)= 55 ppm. The M2 fraction of dark brownish yellow color oil, was identified by LC-MS and IH NMR, as 2,3-dihydroxypropylpentadecanoate.Key words: Palaquium sp., antifungal, Schizophyllumcommune Fries, Pleurotus ostreatus, 2,3-dihydroxypropylpentadecanote.